Ultrasound therapy of diabetes mellitus type 2 - Samosiuk, I.; Zubkova, S.; Chuhraeva, E.; Samosiuk, N.; Zukow, W. (Journal of Education, Health and Sport, 2011)
We studied the possibility of low-frequency UST in the correction of carbohydrate metabolism by assessing levels of fasting glucose and Cpeptide, as well as the content of the contrinsuline hormones (cortisol, samatotropin) in groups of diabetic patients. Ultrasonic treatment was carried out at 44 kHz and amplitude of oscillations 2 microns using the therapeutic device MIT-11 on the projection area of the pancreas stable technique, 5 times per week, exposure to the session for 3 minutes. As the contact material used liquid paraffin. To enhance the effect further impacted on the segmental zone Th7-Th12 labile technique for 2 min. for each area to the left and right. The treatment course consisted of 8-10 sessions. Patients were followed for 12 months. Ultrasonic treatment was carried out against lowering drug therapy, 91 patients aged 18-78 years, including type 1 diabetes was observed in 23 individuals (control group), and type 2 - 68 people. First identified diabetes was diagnosed in 47 patients, the remaining 44 suffered from more than 5 years. Before and after treatment were studied basal levels of C-peptide, cortisol and growth hormone (GH) in serum of venous blood radio immunoassay, we determined the glycemic profile and blood sugar levels in daily urine. Analysis of results showed that 82% surveyed, under the influence of treatment was recorded reduction of hyperglycemia with newly diagnosed diabetes type 1 diabetes and type 2, as well as a long ill patients. Blood glucose levels prior to treatment during the day ranged from 10-15 mmol / l after the treatment - 6.10 mg / dL. The resulting dynamics parameters after UST during observation showed an improvement insulinoproductive function of the pancreas under the influence of ultrasound exposure, which contributed to a more rapid onset of diabetes compensation and reduce the dose glucose-lowering drugs. UST is combined with many kinds of physiotherapy effects: electrotherapy, massage, balneotherapy, laser-and SWT-therapy and other options for therapy with electromagnetic waves, enhancing their effect. This kind of treatment so far has not found wide application in the treatment of diabetes and its complications, however, is a promising method of physiotherapy treatment, given its mechanism of action and different ways of application.